Controllable growth of durable superhydrophobic coatings on a copper substrate via electrodeposition1. Issue 16 (28th April 2015) - He, Ge; Lu, Shixiang; Xu, Wenguo; Szunerits, Sabine; Boukherroub, Rabah; Zhang, Haifeng
<x xml:space="preserve">Abstract</x> Durable superhydrophobic coatings with excellent properties were created via facile and time-saving electrodeposition combined with annealing without organic modification.